Identifying patients with CKD risk at the time of nephrectomy: When to initiate nephrology consult. Issue 2 (June 2021) - Yang, Yihe; Kozel, Zachary; Sharma, Purva; Yaskiv, Oksana; Torres, Jose; Pandya, Shashank; Jhaveri, Kenar D.; Bhaskaran, Madhu; Vira, Manish; Bijol, Vanesa
Introduction: The prevalence of chronic kidney disease (CKD) is high among kidney neoplasm patients because of the overlapping risk factors. Our purpose is to identify kidney cancer survivors with higher CKD risk. Methods: We studied a retrospective cohort of 361 kidney tumor patients with partial or radical nephrectomy. Linear mixed model was performed. Results: Of patients with follow-up >3 months, 84% were identified retrospectively to fulfill criteria for CKD diagnosis, although CKD was documented in only 15%. Urinalysis was performed in 205 (57%) patients at the time of nephrectomy. Multivariate analysis showed interstitial fibrosis and tubular atrophy (IFTA) >25% ( p = 0.005), severe arteriolar sclerosis ( p = 0.013), female gender ( p = 0.024), older age ( p = 0.012), BMI ⩾ 25 kg/m 2 ( p < 0.001), documented CKD ( p < 0.001), baseline eGFR ⩽ 60 ml/min/1.73 m 2 ( p < 0.001), and radical nephrectomy ( p < 0.001) were independent risk factors of lower eGFR at baseline and during follow-up. Average eGFR decreased within 3 months post nephrectomy. However, patients with different risk levels showed different eGFR time trend pattern at longer follow-ups. Multivariate analysis of time × risk factor interaction showed BMI, radical nephrectomy and baseline eGFR had time-dependent impact. BMI ⩾ 25 kg/m 2 and radical nephrectomy were associated with steeper eGFR decrease slope. In baseline eGFR > 90 ml/min/1.73 m 2 group, eGFR rebounded to pre-nephrectomy levels during extended follow-up. In partial nephrectomy patients with baseline eGFR ⩾ 90 ml/min/1.73 m 2 ( n = 61), proteinuria ( p < 0.001) and BMI ( p < 0.001) were independent risk factors of decreased eGFR during follow up. Conclusions: As have been suggested by others and confirmed by our study, proteinuria and CKD are greatly under-recognized. Although self-evident as a minimum workup for nephrectomy patients to include SCr, eGFR, urinalysis, and proteinuria, the need for uniform applications of this practice should be reinforced. Non-neoplastic histology evaluation is valuable and should include an estimate of global sclerosis% (GS) and IFTA%. Patients with any proteinuria and/or eGFR ⩽ 60 at the time of nephrectomy or in follow-up with urologists, and/or >25% GS or IFTA, should be referred for early nephrology consultation.